Pelatihan Pembuatan Keripik Pisang dalam Meningkatkan Pendapatan Keluarga di Desa Rambu-Rambu - Rola Pola Anto; Sitti Rahmatyah; Muhammad Amir; Gunawan Gunawan; La Ode Sahili (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2022)
Rambu-Rambu Village, Laeya District, South Konawe Regency, has the potential of human resources and natural resources that encourage economic progress and prosperity in the village. The problem faced is that the potential of human resources has not been able to take advantage of agricultural or plantation products such as bananas which are quite abundant. The creative and innovative spirit of the community members to process bananas as a product that has high value and sources of family income is still minimal. The problem faced by the community is that the selling price of raw and ripe bananas is very cheap, so they cannot be relied on as a source of family income. The lack of knowledge and skills and the entrepreneurial spirit of the community members to process bananas into products that have high selling value, is a consideration for the implementing team from the Institute for Research and Community Service, Lakidende University to conduct training on making banana chips in Rambu-Rambu Village. The purpose of the training in making chips is to provide basic knowledge and skills on how to process bananas into chips for the residents of Rambu-Rambu Village. The methods used in the training activities are lecture, demonstration and question and answer methods. The stages of implementing the activity are an explanation of the importance of utilizing bananas as a valuable product, the objectives and benefits of training in making banana chips, then the stages of peeling banana skins, slicing bananas, frying, mixing various flavors, packaging and installing banana chips name labels. The results of the evaluation of the banana chip making training that all participants were very satisfied, enthusiastic, and could increase their knowledge, skills and get many benefits. In addition, the trainees were motivated to start a banana chip business to increase family income